Istota i zakres obowiązków informacyjnych dostawców usług płatniczych: [The nature and scope of the information duties of payment service provides] (Studia Prawnicze / The Legal Studies, 2011)
Na wstępie należy podkreślić, że wskazana w tytule problematyka dotyczy relacji prawnych jakie powstają pomiędzy dostawcą usług płatniczych a każdym użytkownikiem tych usług płatniczych. Tym niemniej dyrektywa (jak i ustawa) zezwala na zmodyfikowanie zakresu obowiązku informowania, w zależności od statusu użytkownika usługi płatniczej. Wskazany obowiązek informowania jest najszerszy wówczas, gdy użytkownikiem usługi płatniczej jest konsument. Pojęcie konsumenta zostało zdefiniowane w dyrektywie i oznacza „osobę fizyczną, która w ramach umów o usługę płatniczą objętą niniejsza dyrektywą, działa w celach innych niż jego działalność handlowa, gospodarcza lub zawodowa”. W ustawie nie zdefiniowano pojęcia konsumenta. W tej sytuacji należy odnieść się do defi nicji konsumenta zawartej w kodeksie cywilnym. W obrocie profesjonalnym, a więc wówczas, gdy użytkownikiem usługi płatniczej nie jest konsument, strony umowy o usługi płatnicze, mogą zadecydować o odstąpieniu od wymogu przekazywania przez dostawcę, informacji w takim zakresie jaki jest przewidziany, gdy tym użytkownikiem jest konsument. W obrocie profesjonal-nym węższy zakres obowiązku informowania, odmienny od tego wskazanego w dyrektywie, może być wynikiem porozumienia stron umowy. Tak więc, szeroko ujęty obowiązek dostawcy usług płatniczych, informowania użytkownika tych usług, jest w głównej mierze odniesiony do konsumenta usług płatniczych - osoby fizycznej, która podejmuje czynności prawne nie związane bezpośrednio z jej działalnością gospodarczą czy zawodową. Warto jednak zawrócić uwagę, że dyrektywa zezwala, aby państwa członkowskie w przepisach krajowych wprowadziły obowiązek informowania, o takim samym zakresie, jak w przypadku relacji z konsumentem, gdy użytkownikiem usługi płatniczej jest mikroprzedsiębiorca. Problem concerning the duties, of payment service providers to provide information have been regulated mainly by Directives 2007/64/EC of the European Parliament and of the Council of 13 November 2007 on payment services in the internal market amending Directives 97/7/EC, 2002/65/EC, 2005/60/EC and 2006/48/EC and repealing Directive 97/5/EC. The provisions of the Directive have been implemented into the Polish legal system in the Act on Payment Services, adopted on 18 August 2011 (Dz.U. Nr 199, poz. 1175). These acts contain the legal solutions creating the legal framework for the single market for payment services. The adoption of the Directive took place in the implementation of the concept of a single market in financial services, but at the same time the Directive aims at protection consumer rights. The provisions of the Directive and Act on Payment Services define both the principle of establishment of new payment services providers to the market, as well as rules concerning transparency of conditions and information requirements for payment services, and the respective rights and obligations of payment service users and payment service providers. The Directive and the Act on Payment Services impose on payment services providers far-reaching duties to inform users. These Acts specify the obligations on payment service providers as regards the provision of information to the payment service users who should receive the same high level of clear information about payment services in order to make well-information choices and be able to shop around within the UE. Payment service providers are obliged to, in an easily accessible manner, make available or provide to the payment service user, pre-contractual information and conditions (prior general information). Immediately after execution of the payment transaction, the payment service provider shall provide or make available to the payee the information about transaction. Then immediately after the execution of the payment transaction, the payment service provider shall provide or make available to the payee, the information about transaction. The obligation of payment service provider to make available or provide the information, has its legal basis in the legal standard and corresponds to user’s right to obtain such information based on the legal norm. It is therefore important to consider the legal essence of duties to provide information, as well as the scope of information requirements.